Práctica ritual del veneno de sapo acate en la comunidad nativa Matsés Buenas Lomas Antigua 2021 - Tumi Dësi, Roldan Dunu (2022)
The present investigation entitled "Ritual practice of the application of the poison of the Acate toad in the Matsés Buenas Lomas Antigua Native Community - 2022", was developed in one of the oldest Communities of the Matsés indigenous people. Its main objective is to describe the healing ritual practice of the resin of the Acate toad in the native community of Matsés Buenas Lomas Antigua. The methodology used in this research was a qualitative approach since it sought to understand the ritual practice of the resin of the toad acate through information narrated by the Matsés actors. For ethnography or data collection technique in the field they were the following: participant observation, unstructured interview and semi-structured interview. To carry out this research, the oldest specialists between 81 and 30 years old, and also the young people between 17 and 29 years old, who administer the resin of the acate toad, were the key informants, having a total of 23 interviewees. The results of the research show that the practice of the resin of the Acate toad is a constitutive part of the formation of the Matsés person through which the generation of greater experience (grandparents and older adults), who has achieved social recognition for being great specialist in knowing how to do an activity or recognized as a worker, she transmits her ability and positive values to the young generation (boys, girls, adolescents and adults).